A mulher no mercado de trabalho e na liderança das organizações: uma análise bibliométrica no campo da administração - Nascimento, Cleonice Nazaré do (2015)
In 21st century one observes more interest by organisations in subjects related to the female presence in labor market, specifically in leadership, entrepreneurship positions as well as executive and strategic functions, what is a topic approached constantly in diverse publications in business area in journals, articles and events. The present thesis, which involves bibliometric analysis, aimed at studying the matter of gender in organizations focusing women in labor market and in leadership in administration field. For such accomplishment, specific objectives were established which were: getting bibliometric indicators in Web of Science database from 2005 to 2015; quantifying and identifying articles, authors, citations occurrence, journals and their relevance, language, key words, institutions, publications country, editors and investigating other complementing topics discussed by the most relevant articles. The methodology used for such research work includes tools with both qualitative and quantitative, by secondary and exploratory data, that generates two bibliometric studies of the scientific articles. For the development of the proposed study here groups of key words were structured for each topic and search in the referred data base. The first bibliometric analysis, about the topic women in labor market resulted 11 articles. The most subtopics of the most relevant articles were: gender versus performance, women economic empowerment, entrepreneurship and impact factors for women in strategic positions. The second bibliometric analysis about the topic female leadership in organizations resulted in 30 articles, almost over three times the amount of the previous topic. The subtopics of the most relevant articles brought the matter of gender, focusing women in subjects related mostly to: leadership versus success; difficulties in career improvement; leadership stereotypes; presence in political functions; overrepresentation in strategic functions and professional and personal life balance